Comparative studies of vertebrate iduronate 2-sulfatase (IDS) genes and proteins: evolution of A mammalian X-linked gene - Holmes, Roger S. (3 Biotech, 2017)
IDS is responsible for the lysosomal degradation of heparan sulfate and dermatan sulfate and linked to an X-linked lysosomal storage disease, mucopolysaccharidosis 2 (MPS2), resulting in neurological damage and early death. Comparative IDS amino acid sequences and structures and IDS gene locations were examined using data from several vertebrate genome projects. Vertebrate IDS sequences shared 60–99% identities with each other. Human IDS showed 47% sequence identity with fruit fly (Drosophila melanogaster) IDS. Sequence alignments, key amino acid residues, N-glycosylation sites and conserved predicted secondary and tertiary structures were also studied, including signal peptide, propeptide and active site residues. Mammalian IDS genes usually contained 9 coding exons. The human IDS gene promoter contained a large CpG island (CpG46) and 5 transcription factor binding sites, whereas the 3′-UTR region contained 5 miRNA target sites. These may contribute to IDS gene regulation of expression in the brain and other neural tissues of the body. An IDS pseudogene (IDSP1) was located proximally to the IDS gene on the X-chromosome in primate genomes. Phylogenetic analyses examined the relationships and potential evolutionary origins of the vertebrate IDS gene. These suggested that IDS has originated in an invertebrate ancestral genome and retained throughout vertebrate evolution and conserved on marsupial and eutherian X-chromosomes, with the exception of rat Ids on chromosome 8. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13205-016-0595-3) contains supplementary material, which is available to authorized users.